Intimate Partner Violence Against Women Among North Korean Refugees: A Comparison With South Koreans. Issue 15 (August 2020) - Nam, Boyoung; Kim, Jae Yop; Ryu, Wonjung
North Korean refugees in South Korea have been reported as at higher risk of intimate partner violence (IPV). However, few studies have examined risk factors of IPV among North Korean refugees. This study aimed to report the prevalence of IPV against women among North Korean refugees, and compared the risk factors of IPV against women between South Koreans and North Korean refugees in South Korea. Data from a nationwide survey about domestic violence in South Korea were used. The rate of IPV against women by North Korean refugees was 57.1%, which is considerably higher than that of South Koreans (9.9%). The regression analysis indicated that North Korean refugees perpetrated partner violence against women more frequently than South Koreans, even after controlling for socioeconomic factors. Child abuse victimization and witnessing IPV between parents were the main factors of IPV against women among South Koreans. On the other hand, stress and a tolerant attitude toward using violence were significantly associated with IPV against women among North Korean refugees. The findings suggested that stress management and education on reducing tolerance to violence should be provided to prevent IPV against women among North Korean refugees.